ANALISIS KONTRIBUSI BUDIDAYA TEMBAKAU TERHADAP PROFITABILITAS PETANI - Riduwan, Riduwan (Universitas Gajah Putih, 2022)
Tobacco cultivation is a livelihood for farmers who are in an area or area of ​​​​Rayung village, Senori district, Tuban district, East Java province. Tobacco plants are cultivated by farmers during the dry season, with the desire to be able to maximize their income. The purpose of this research is to be able to analyze the level of income as well as the level of profitability of agriculture that cultivates tobacco and the gap in income and profitability between agriculture that cultivates rice, corn, kale, soybeans and watermelon and the methodology applied in the current study is a survey. (simple random sampling) is the methodology used in the current study. There are (45 farmers) selected as respondents. Characteristics of respondent data were analyzed using a descriptive analysis system, and the use of income calculations and profitability of tobacco cultivation were analyzed using agricultural sector analysis. The data were tested using the appropriate sample t-test and sample t-test. As a result, the income and profitability of tobacco cultivation per season is Rp. 26,500,000, while cultivation other than tobacco is Rp. 15,450,000, maize cultivation is Rp. 17,200,000, kale cultivation is Rp. 11,150,000, and soybean cultivation is Rp. 9,750,000. . Watermelon cultivation Rp. 14,150,000. The profitability of tobacco cultivation is 194.49%, which means it is very profitable compared to rice, corn, kale, soybeans and watermelon. There is a difference between the income of tobacco cultivation and the income of the cultivation of rice, corn, kale, soybeans and watermelon